2015
DOI: 10.3390/rs70302971
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of UAV, Aircraft and Satellite Remote Sensing Platforms for Precision Viticulture

Abstract: Precision Viticulture is experiencing substantial growth thanks to the availability of improved and cost-effective instruments and methodologies for data acquisition and analysis, such as Unmanned Aerial Vehicles (UAV), that demonstrated to compete with traditional acquisition platforms, such as satellite and aircraft, due to low operational costs, high operational flexibility and high spatial resolution of imagery. In order to optimize the use of these technologies for precision viticulture, their technical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
294
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 534 publications
(357 citation statements)
references
References 24 publications
9
294
0
7
Order By: Relevance
“…The key strengths of UAV are the high spatial ground resolution and a reduced planning time, which allows for highly flexible and timely vineyard monitoring [15,[38][39][40]. This study presents results using different classifications methods to detect and segment the vine canopy in ultra-high-resolution RGB imagery obtained from UAV.…”
Section: Perspectives and General Study Limitationsmentioning
confidence: 99%
“…The key strengths of UAV are the high spatial ground resolution and a reduced planning time, which allows for highly flexible and timely vineyard monitoring [15,[38][39][40]. This study presents results using different classifications methods to detect and segment the vine canopy in ultra-high-resolution RGB imagery obtained from UAV.…”
Section: Perspectives and General Study Limitationsmentioning
confidence: 99%
“…Berni et al [28,29] suggested that the two critical limitations for using current satellite sensors in real-time crop management are the lack of imagery having optimum spatial and spectral resolution and unfavorable revisit times for many crop stress-detection applications. In addition, Matese et al [30] indicated that low-resolution images of traditional acquisition platforms fail to represent much of the intra-vineyard variability that is a key for application of the site-specific management (precision viticulture) of heterogeneous vineyards.…”
Section: Introductionmentioning
confidence: 99%
“…Matese et al [7] provided an intercomparison of the acquisition and processing costs of three different platforms (UAS, Aircraft, and Satellite). Their cost model parametrization allows the derivation of the relative cost for the different configurations, showing that UAS is the most cost-effective solution for fields of an extent equal to or less than 20 ha.…”
Section: Introductionmentioning
confidence: 99%